Respostas
respondido por:
4
y= ax + b
1= 0a + b
y= ax + b
0= -3a + b
sendo assim basta criar um sistema, fica:
1= 0a + b
0= -3a + b
b= 3a substituindo,
1= 0a + 3a ---> a = 1/3
b= 3a ---> b= 3(1/3) ---> b= 1
sabendo que a= 1/3 ; b= 1 e a lei de formação seja F(x) = ax + b, a função do 1 grau é:
F(x) = 1/3x + 1.
1= 0a + b
y= ax + b
0= -3a + b
sendo assim basta criar um sistema, fica:
1= 0a + b
0= -3a + b
b= 3a substituindo,
1= 0a + 3a ---> a = 1/3
b= 3a ---> b= 3(1/3) ---> b= 1
sabendo que a= 1/3 ; b= 1 e a lei de formação seja F(x) = ax + b, a função do 1 grau é:
F(x) = 1/3x + 1.
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás